1995
DOI: 10.1016/0014-5793(95)01065-m
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage by t‐butyl hydroperoxide causes DNA single strand breaks which is not linked to cell lysis. A mechanistic study in freshly isolated rat hepatocytes

Abstract: In rat hepatoeytes, DNA damage by t-butyl hydroperoxide (tBOOH) was measured by using the fluorimetric analysis of alkaline DNA unwinding. The electrophoretic profile of genomic DNA suggests single rather than double DNA strand breaks formation. Oxidative DNA modifications, measured as increased 8-hydroxy-deoxyguanosine content, were not detected. Lysis of hepatocytes and DNA strand breaks induced by tBOOH did not correlate, indicating that both processes are not interconm~ted. Since o-phenantbroline prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 31 publications
(29 reference statements)
2
38
0
3
Order By: Relevance
“…t-BHP induces DNA breaks in many cell types 20,21 and can induce both "stress-induced premature senescence," and accelerate telomere shortening of human VSMCs. 2 t-BHP increased oxidant stress, DNA breaks and P-ATM and ␥-H2AX expression in normal VSMCs to levels seen in plaque VSMCs, suggesting that plaque VSMCs might be subject to chronic oxidant stress (data not shown).…”
Section: Atorvastatin Accelerates Dna Repair In Human Vsmcsmentioning
confidence: 99%
“…t-BHP induces DNA breaks in many cell types 20,21 and can induce both "stress-induced premature senescence," and accelerate telomere shortening of human VSMCs. 2 t-BHP increased oxidant stress, DNA breaks and P-ATM and ␥-H2AX expression in normal VSMCs to levels seen in plaque VSMCs, suggesting that plaque VSMCs might be subject to chronic oxidant stress (data not shown).…”
Section: Atorvastatin Accelerates Dna Repair In Human Vsmcsmentioning
confidence: 99%
“…We next examined oxidative stress in plaque and normal VSMCs, in normal VSMCs at replicative senescence, and after treatment of VSMCs with tert-butylhydroperoxide (t-BHP), an inducer of hydrogen peroxide 21 that can induce DNA single-strand breaks. 22,23 Flow cytometric analysis of fluorescence of the redox-sensitive dye H 2 -DCFDA showed significantly increased oxidative stress in plaque versus normal VSMCs and also in normal VSMCs at replicative senescence. These changes paralleled a significant increase in mitochondrial mass in plaque and senescent VSMCs (supplemental Figure II).…”
Section: Matthews Et Al Atherosclerosis and Telomere Shortening 159mentioning
confidence: 99%
“…In particular, 3 is a rare substance on which only one study has reported. 7) Compound 4 was assigned to be eriodictyol-7-O-b-D-glucopyranoside on the basis of UV, MS, 1 H-NMR and 13 C-NMR spectral data. 8) The CD spectrum of 4 showed a positive Cotton eŠect at 292 nm and a negative Cotton eŠect at 333 nm.…”
mentioning
confidence: 99%
“…This system involves the bacteria receiving fatal damage through lipid peroxidation of the membranes, and the DNA single strand breaking. 13) Table 1 shows the protective activity of the isolated compounds against the peroxyl radical. The present study demonstrates that orientin and isoorientin signiˆcantly protected bacteria from the bactericidal action of peroxyl radicals, although their activities were lower than that of epigallocatechin gallate.…”
mentioning
confidence: 99%